Znaczenie antyku. Siedem sztuk wyzwolonych - Dürüşken, Çiğdem (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The article aims to address the meaning of Antiquity as it appears in the educational system of this most influential civilization.